Pyrosequencing of supra- and subgingival biofilms from inflamed peri-implant and periodontal sites - Schaumann, Simone; Staufenbiel, Ingmar; Scherer, Ralph; Schilhabel, Markus; Winkel, Andreas; Stumpp, Sascha Nico; Eberhard, Jörg; Stiesch, Meike (BMC oral health, 2014)
To investigate the microbial composition of biofilms at inflamed peri-implant and periodontal tissues in the same subject, using 16S rRNA sequencing. Supra- and submucosal, and supra- and subgingival plaque samples were collected from 7 subjects suffering from diseased peri-implant and periodontal tissues. Bacterial DNA was isolated and 16S rRNA genes were amplified, sequenced and aligned for the identification of bacterial genera. 43734 chimera-depleted, denoised sequences were identified, corresponding to 1 phylum, 8 classes, 10 orders, 44 families and 150 genera. The most abundant families or genera found in supramucosal or supragingival plaque were Streptoccocaceae, Rothia and Porphyromonas. In submucosal plaque, the most abundant family or genera found were Rothia, Streptococcaceae and Porphyromonas on implants. The most abundant subgingival bacteria on teeth were Prevotella, Streptococcaceae, and TG5. The number of sequences found for the genera Tannerella and Aggregatibacter on implants differed significantly between supra- and submucosal locations before multiple testing. The analyses demonstrated no significant differences between microbiomes on implants and teeth in supra- or submucosal and supra- or subgingival biofilms. Diseased peri-implant and periodontal tissues in the same subject share similiar bacterial genera and based on the analysis of taxa on a genus level biofilm compositions may not account for the potentially distinct pathologies at implants or teeth.